The impact of language technologies in the legal domain - Trancoso, I. (2023)
In the current digital era, language technologies are playing an increasingly vital role in the legal domain, assisting users, lawyers, judges, and legal professionals to solve many real-world problems. While open datasets and innovative deep learning methodologies have led to recent breakthroughs in the area, significant efforts are still being made to transfer the theoretical/algorithmic developments, associated with general text and speech processing, into real applications in the legal-domain. This chapter presents a brief survey on language technologies for addressing legal tasks, covering studies and applications related to both text and speech processing.